The partial contribution of CO2-emission losses from subsidence in small-holder oil palm plantation on a tropical peatland in West Kalimantan, Indonesia - DWI ASTIANI; TRI WIDIASTUTI; HANNA ARTUTI EKAMAWANTI; WIWIK EKYASTUTI; EMI ROSLINDA; MUJIMAN MUJIMAN (Society for Indonesian Biodiversity, 2022)
Abstract. Astiani D, Widiastuti T, Ekamawanti HA, Ekyastuti W, Roslinda E, Mujiman. 2022. The partial contribution of CO2-emission losses from subsidence in small-holder oil palm plantation on a tropical peatland in West Kalimantan, Indonesia. Biodiversitas 23: 6539-6545. Carbon storage in tropical peat ecosystems over thousands of years, especially within peat soil, is in huge quantity. Degradation of peat ecosystems is generally caused by human factors, whether intentional or not, damaging the carbon storage function of tropical peatlands, where forest clearing, drainage development, and burning of land converted to agriculture and plantations result in significant greenhouse gas emissions. Tropical peat in the Kubu Raya District of West Kalimantan, which has a relatively large area of peat, has been degraded as a cause of uncontrolled drainage and land fires caused by a lack of management after its forest cover was lost. The main impact is an increase in peat CO2 emissions due to changes in land use, especially lowering groundwater levels. Subsequently, the subsidence process also occurs after land clearing. This study aims to obtain the proportion of carbon biomass loss due to the CO2 emission process from reducing the peat layer due to subsidence. Data collection was executed for two years, where CO2 emission was monitored bi-weekly, and the subsidence was measured bi-monthly. The results demonstrate groundwater levels dictate the peat CO2 emission and subsidence. Lowering GWL 30 to -85 cm increases CO2 by more than three times, approximately. The rate of peat subsidence shows similar trends to the emission. The proportion of peat biomass loss on CO2 emission was between 58.9 to 73.5%, except for GWL 5 cm, where the proportion was the highest at 82%. The results of this study are beneficial in explaining the part of the subsidence that impacts the sources of CO2 emissions from the small-holder oil palm and GWL management on peatlands.